Implicit intelligence among middle school students (Journal of the College of Basic Education, 2022)
The current research aims at measur Implicit Intelligence among middle school students. the significance of statistical differences in Implicit Intelligence among middle school students according to the gender variable and the variable of specialization (scientific – literary) was selacted. The research sample was chosen from middle school astudents belonging to the first Karkh Education Directorarte(250) males and(250)females and scientific and literary sciences .To achieve the research objectives ,the researcher built the measure of Implicit Intelligence. the The data were statistically analyzed using the statistical bag (SPSS) (T=0.66) ,which is greater than the T- table value of 1.96 .This means that the students have an Implicit Intelligence.The researcher used the T- test for two independent samples to identify second target The results showed no statistically significant differences between males and females .the calculated T value ( 0.878) is smaller than the tabular T Value of ( 1.96 ) .The results showed no statistically significant differences in Implicit Intelligence according to the specialization variable (scientific – literary) The calculated T value ( 0.271) is smaller than the table value ( 1.96 ) .In the light of the results, the researcher found a number of recommendations and suggestions.